2013
DOI: 10.1364/ao.52.006445
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and analysis of water vapor inside optical components for optical fiber H2O sensing system

Abstract: Water vapor existing inside internal end-face gaps of optical components of an optical fiber H2O sensing system makes it possible to influence the measurement accuracy and stability. The influence principle has been briefly analyzed based on the structure of three main optical components: a distributed feedback laser diode (DFB-LD), a collimator, and a photoelectric diode (PD). With application of a differential technique, the influence of water vapor inside the DFB-LD can be removed. With reasonable recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…According to the analysis in [8], the water vapor inside the optical components can influence the measurement result. Combined with (5) in the WMS technique, the influenced expression of the water vapor concentration should be…”
Section: Analysis Of Reliability and Resolution Improvementmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the analysis in [8], the water vapor inside the optical components can influence the measurement result. Combined with (5) in the WMS technique, the influenced expression of the water vapor concentration should be…”
Section: Analysis Of Reliability and Resolution Improvementmentioning
confidence: 99%
“…To fully exhibit the influence of the water vapor inside the optical components especially the improvement of reliability and resolution, a comparison research was demonstrated experimentally between the normal transmissiontype gas cell with a 10-cm effective path length [8] and Herriot gas cell with a 3-m effective path length. Figure 3(a) shows the structure of the normal gas cell comprising two commercial fiber collimators used in communication.…”
Section: Reliability and Resolution Improvementmentioning
confidence: 99%
See 1 more Smart Citation
“…We presumed that the disproportion was due to background absorption of water vapor inside optical components in the system, and some previous work had been done to talk about the water vapor inside optical components. Further processing was done on the results of the experiment [15] to eliminate the effects of the water vapor inside the optical components as follows: Obviously, any concentration can be used as a reference to eliminate the effects of water vapor inside optical components in theory, but we are accustomed to taking the lowest concentration. So we chose 15 ppm concentration signal as the reference to eliminate the water vapor inside optical components as Eq.…”
Section: A Concentration Measurement and Linear Analysismentioning
confidence: 99%
“…Thus, we can conclude that a reference absorption should be required for any water vapor detection system for inducing errors. Taking the water vapor absorption inside the optical components as a reference to measure water concentration was a good idea and had been discussed [15].…”
Section: A Concentration Measurement and Linear Analysismentioning
confidence: 99%